17 Cell viability after DMEK preparation. (16th November 2022) - Sajet, Anita; Miron, Alina; Beek, Esther Groeneveld-van; Kok, Jet; Dedeci, Mehtap; Jong, Maloeke de; Melles, Gerrit; Oellerich, Silke; Wees, Jacqueline van der
Abstract : Purpose: To evaluate the effect of graft preparation and organ-culture storage on endothelial cell density (ECD) and viability of Descemet membrane endothelial keratoplasty (DMEK) grafts. Methods: DMEK grafts (n=27) were prepared at Amnitrans EyeBank Rotterdam from 27 corneas (15 donors) that were eligible for transplantation but could not be allocated due to the COVID-19-related cancellation of elective surgeries. Cell viability (by Calcein-AM staining) and ECD of 5 grafts originally scheduled for transplantation, were evaluated on the originally planned surgery day, whereas 22 grafts from paired donor corneas were evaluated either directly post-preparation or after 3-7 days of storage. ECD was analyzed by light microscopy (LM ECD) and Calcein-AM staining (Calcein-ECD) Results: Light microscopy (LM) evaluation of all grafts showed an unremarkable endothelial cell monolayer directly after preparation. However, median Calcein-ECD for the 5 grafts initially allocated for transplantation was 18% (range 9-73%) lower than median LM ECD. For the paired DMEK grafts, Calcein-ECD determined by Calcein-AM staining on the day of graft preparation and after 3-7 days of graft storage showed a median decrease of 1% and 2%, respectively. Median percentage of central graft area populated by viable cells after preparation and after 3-7 days of graft storage was 88% and 92%, respectively. Conclusions: Cell viability of most of the grafts will not be affected by preparation and storage. Endothelial cell damage may be observed for some grafts within hours after preparation with insignificant additional ECD changes during 3-7 days of graft storage. Implementing an additional post-preparation step in the eye bank to evaluate cell density before graft release for transplantation may help to reduce postoperative DMEK complications